Technical and vocational education and training in the Philippines in the age of industry 4.0. (Public private partnership monitor.)
New and emerging technologies under Industry 4.0 are rapidly changing the nature of work and demand for skills around the world. Meanwhile, the coronavirus disease (COVID-19) is causing significant labor market upheavals. The report assesses what needs to be done to ensure the country TVET system, and TESDA, the agency responsible for TVET, can adapt to these rapid technological developments and also mitigate the negative impacts to the labor market.